Addressing essential skills gaps among participants in an OHS training program: a pilot study. Issue 2 (2nd July 2020) - Saunders, Ron; Cardoso, Siobhan; Le Pouésard, Morgane; Breslin, Curtis; Myers, Karen; Swift, Michael; Collins, Tracy
Abstract: The Government of Canada and other agencies have validated nine dimensions of 'Essential Skills' (ES) including reading, document use, and numeracy. ES gaps can impede the effectiveness of occupational health and safety (OHS) training. The purpose of our study was twofold: to explore whether OHS learning could be enhanced by integrating curriculum to address ES gaps within a safety training programme, and to identify challenges in applying what is learned to the work site. We piloted this approach within an OHS training programme for riggers of loads that crane operators lift. There was some quantitative evidence that the intervention improved learning, but the sample was small. The qualitative findings from interviews and focus groups indicated a disconnect between training and worksite practices, including using shortcuts instead of calculating safe loads. We produced a guide for those who may wish to try a similar intervention.